2019
DOI: 10.3390/met9040404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermodynamic Melt Formation Characteristics on Liquid Phase Fluidity of Iron Ore in the Sintering Process

Abstract: The liquid phase fluidity of iron ore is a vital index of fundamental sintering characteristics. In this paper, FactSage software and a visible microsintering test device were used to research the influence of the thermodynamic melt characteristics on the liquid phase fluidity under fixed CaO content conditions. The results show that the laws governing liquid phase fluidity of iron ore are significantly different with a fixed alkalinity and fixed CaO content of the sample. The liquid phase content at the sinte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…It is found that high Al 2 O 3 content tends to promote the lowest assimilation temperature and namely weakens the assimilability [18,19]. Increased alumina concentration increases the viscosity and decreases the fluidity of liquid phase [20,21,27,28]. According to the previous studies [22][23][24]29], the increasing Al 2 O 3 content contributes to the formation of SFCA, leading to a higher proportion of SFCA in sinter.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…It is found that high Al 2 O 3 content tends to promote the lowest assimilation temperature and namely weakens the assimilability [18,19]. Increased alumina concentration increases the viscosity and decreases the fluidity of liquid phase [20,21,27,28]. According to the previous studies [22][23][24]29], the increasing Al 2 O 3 content contributes to the formation of SFCA, leading to a higher proportion of SFCA in sinter.…”
Section: Introductionmentioning
confidence: 88%
“…In order to determine the liquid phase fluidity of the eight iron ores, the iron ore sample and Ca(OH) 2 pure reagent were mixed with water at 4.0 basicity and compressed into tablets with 10 mm in diameter and 8 mm in height at a set pressure of 200 N. After dried, the ore tablet was placed up on the corundum tablet with 40 mm in diameter and 2 mm in height and then put into the horizontal tube furnace, roasted at 1310 • C for 5 min in the air atmosphere. After cooled to room temperature via the same cooling method, the liquid phase fluidity index was measured according to the literature [27]. The higher fluidity index contributed to the better liquid phase fluidity.…”
Section: Liquid Phase Fluiditymentioning
confidence: 99%
See 1 more Smart Citation
“…Sinter and pellets are the most common iron-containing burden for blast furnaces, the proportion of sinter and pellets exceeds 90% of the blast furnace burden, and modern blast furnaces burden contains a little lump ore to balance the slag system [1,2]. A total of 70% high basicity sinter and 30% acid pellets are a general burden structure in China [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Yamaoka and Kawaguchi [8] discussed 3D variations on sinter properties produced on a pot apparatus experimental facility and presented a mathematical model based on the transport phenomena to simulate the experimental conditions in the sintering process. The melt formation temperature, liquid phase content, and liquid viscosity under different sintering temperatures were simulated to study the influence of these thermodynamic melt formation characteristics on the liquid phase fluidity of iron ore in the sintering process [9]. Most modelling processes worldwide deal with heat generation and transfer, melt formation, and sinter cooling.…”
Section: Introductionmentioning
confidence: 99%